Tactile graphics exploration studies using fingertip tracking based on colour markers detection for visually impaired people - Shamsul Bahrin, Muhammad Ikmal Hakim; Md. Yusof, Hazlina; Sidek, Shahrul Na'im (IEEE, 2020)
It is very difficult for people with visual impairment and blindness to access visual information. Thus, tactile graphics became one of the alternatives to help them access maps, graphs, painting, illustration and other graphical materials. However, it is challenging to use tactile graphics. The blind and visually impaired people need to have good exploratory procedures and strategies to gather information tactually. In psychology, several studies have been conducted to clarify how people with visual impairment and blindness perform tactile graphics exploration. But the information is still insufficient, and the studies conducted usually relies on video observation. Therefore, to provide more insight on how people with visual impairment and blindness explore tactile graphics, a fingertip tracking system using Logitech Webcam and MATLAB software has been developed. The method of tracking the fingertips is by using colour markers detection. With the system, the position of the fingertips can be recorded and used for analyzing the tactile graphics exploration activities. It is aimed that this system can be a tool to visualize the cognitive process of people visual impairment and blindness explore tactile graphics materials.